LearnOvation: an intervention to foster exploration and exploitation behaviour in health care management in daily practice - Gunilla Avby; Sofia Kjellström (BMC, 2019)
Abstract Background Innovation has been identified as an important engine for improving the quality, productivity and efficiency of health care. Little is known about how to stimulate innovation capacity in primary health care in general; even less is known about how specific interventions should be designed to support managements' work with practice-based innovations. Research has shown that if managers and teams are excellent at handling the challenges of production (exploitation) and development (exploration), they are better at innovation. The aim of the study is to develop a dynamic management support programme to increase innovation leadership skills in daily practice. Methods The study has an interactive approach that allows the need for empirical and theoretical knowledge to emerge and merge, and a quasi-experimental cross-over design. Eight primary health care centres will participate in the study. In the first phase, the management teams at four health care centres will participate in the intervention, and the other four centres will serve as a control group. Thereafter, the units will switch places and the control group will experience the intervention. All staff at the 8 units will answer questionnaires at four points in time (before, during, after, 6 months later) to evaluate the effects of the intervention. Discussion The study will contribute to knowledge on how to organize processes of innovation and support exploitation and exploration behaviours by co-producing and testing a tailor-made management support programme for innovation work in primary health care. An expected long-term effect is that the support system will be disseminated to other centres both within and beyond the participating organizations.